PERBANDINGAN DOSIS PIRIDOSTIGMIN PERFORMA FUNGSIONAL DAN DERAJAT KLINIS PASIEN MIASTENIA GRAVIS SEBELUM DAN SETELAH TIMEKTOMI - Christianty Sugiarto,* Sobaryati,* Henny Anggraini Sadeli,* Tri Wahyu Murni** (NEURONA, 2018)
INTRODUCTION MYASTHENIA GRAVIS MG IS HIGHLY ASSOCIATED WITH THYMIC ABNORMALITIES MOST CASES SHOW DECREASING DOSAGE OF DRUGS AND IMPROVING OF CLINICAL SYMPTOMS AFTER THYMECTOMY HOWEVER IN INDONESIA THERE ARE ONLY LIMITED NUMBER OF STUDIES HAVE EVALUATED IT